The Reiter protein complement-fixation test using the AutoAnalyzer - Pugh, V. W. (1966)
A method for the Reiter protein complement-fixation test using the Techncon AutoAnalyzer is described. Two hundred and fifty sera were tested, when six false-positive and nine false-negative results were obtained when compared with results obtained by the manual method. Deep freezing the sera before testing on the AutoAnalyzer increased the sensitivity so that in a further 250 sera tested no false-negative and two false-positive results were obtained when compared with the results obtained at the Venereal Diseases Reference Laboratory, London.